2021
DOI: 10.1111/imr.12965
|View full text |Cite
|
Sign up to set email alerts
|

BCG‐induced protection against Mycobacterium tuberculosis infection: Evidence, mechanisms, and implications for next‐generation vaccines

Abstract: Bacillus Calmette-Guérin (BCG) is a live-attenuated vaccine derived from Mycobacterium bovis of the Mycobacterium tuberculosis (Mtb) complex and was first used in medical practice in 1921. It is administered intradermally after birth, while repeat dosing in adolescence and at other stages of life have been adopted inconsistently in different parts of the world. Efficacy trials have yielded hugely variable results, ranging from 0-80% efficacy against TB disease across different locations. 1 Furthermore, the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 208 publications
2
26
0
Order By: Relevance
“…Bacillus Calmette–Guérin (BCG) is a live-attenuated vaccine largely established to protect against childhood meningitis and disseminated tuberculosis (TB) ( Foster et al, 2021 ) Several epidemiological findings suggest that BCG may increase the capacity of the immune system to fight against pathogens other than TB ( Leentjens et al, 2015 ) and such non-specific responses augment both T cell–mediated adaptive and innate immune memory in a process called trained immunity and this could have important implications for improving vaccination strategies. ( Netea and van Crevel, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus Calmette–Guérin (BCG) is a live-attenuated vaccine largely established to protect against childhood meningitis and disseminated tuberculosis (TB) ( Foster et al, 2021 ) Several epidemiological findings suggest that BCG may increase the capacity of the immune system to fight against pathogens other than TB ( Leentjens et al, 2015 ) and such non-specific responses augment both T cell–mediated adaptive and innate immune memory in a process called trained immunity and this could have important implications for improving vaccination strategies. ( Netea and van Crevel, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, based on findings for other mycobacterial diseases (tuberculosis, leprosy), it is not surprising that primary infection does not enhance immune protection against a second exposure [26,27]. The only vaccine currently available for mycobacterial disease is BCG, which does not provide full protection against M. tuberculosis [28]. Furthermore, studies in a mouse model of M. ulcerans infection showed that mice displaying spontaneous healing after a first infection were not protected against a second challenge with M. ulcerans [29].…”
Section: Discussionmentioning
confidence: 99%
“…The only vaccine currently available for mycobacterial disease is BCG, which does not provide full protection against M . tuberculosis [ 28 ]. Furthermore, studies in a mouse model of M .…”
Section: Discussionmentioning
confidence: 99%
“…The function of MycEVs in vivo is less clear. Intra-tracheal administration of EVs released from Mycobacterium bovis BCG, which is an attenuated strain of M. bovis and the only FDA-approved vaccine for Mtb (Foster et al, 2021), leads to an exacerbation of infection when Peptidoglycan (PG) is a polysaccharide made of two glucose derivatives, N-acetylglucosamine (NAG) and N-acetylmuramic acid (NAM), that alternate to form long linear chains. The chains are crosslinked to one another by a tetrapeptide -L-alanine, D-glutamine, L-lysine or mesodiaminopimelic acid (DPA), and D-alaninethat extends from the NAM sugar unit, allowing a lattice-like structure to form.…”
Section: Function Of Mycobacteria-derived Evsmentioning
confidence: 99%